2006
DOI: 10.1159/000088405
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Peritubular Capillary Loss and Altered Expression of Vascular Endothelial Growth Factor in IgA Nephropathy

Abstract: Background/Aims: To determine the roles of peritubular capillary (PTC) loss and expression of vascular endothelial growth factor (VEGF) and its transcription factor, hypoxia-inducible factor-1 (HIF-1), in the progression of IgA nephropathy (IgAN), we analyzed the expression of VEGF and HIF-1, and the number of PTCs in patients with variable severity of IgAN. Methods: Renal biopsy specimens from patients with IgAN (n = 23) were classified according to interstitial injury score: grade 0 (0%), grade 1 (1–25%), gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 56 publications
3
35
0
1
Order By: Relevance
“…Peritubular capillaries (PTCs) were assessed by immunohistochemical analysis using antibodies against CD34, which is an intrinsic endothelial cell antigen (17). As shown in Fig.…”
Section: Peritubular Capillariesmentioning
confidence: 99%
“…Peritubular capillaries (PTCs) were assessed by immunohistochemical analysis using antibodies against CD34, which is an intrinsic endothelial cell antigen (17). As shown in Fig.…”
Section: Peritubular Capillariesmentioning
confidence: 99%
“…Indeed, clinical biopsy studies have shown an association between loss of tubular structure and function on the one hand and capillary rarefaction on the other. 11,12 Because of their limited replicative capacity, renal ECs are thought to be insufficiently capable to completely repair the injured endothelium of the peritubular capillary plexus after IRI. 13,14 Therefore, current therapeutic strategies to prevent microvascular loss have focused on the prevention of pericyte perturbation to reduce capillary rarefaction.…”
mentioning
confidence: 99%
“…15,16) In addition, in the disease control group of this study, PTC networks were decreased, which were also clinically recognized in relation to the histological findings of interstitial injury in IgA nephropathy as a marker of poor prognosis. 17) Furthermore, renal dysfunction and elevated blood pressure were observed in the vehicle group. In a previous report, SKT was administered at doses 1.0 to 2.0 g/kg/d to stroke-prone spontaneously hypertensive rats.…”
Section: Discussionmentioning
confidence: 97%